Effects of 8 months of high-intensity interval training on physical fitness and health-related quality of life in substance use disorder - Tan, Jun; Wang, Jingsong; Guo, Yin; Lu, Chunxia; Tang, Wanke; Zheng, Lan (Frontiers in Psychiatry, 2023)
OBJECTIVE: This study aimed to investigate the effect of 8 months of high-intensity interval training (HIIT) on physical fitness and health-related quality of life in methamphetamine abstainers. Methods: 60 methamphetamine abstainers were randomly assigned to either the HIIT group or the control group according to a random sampling method. The HIIT group received 8 months of four 60-minute sessions per week under supervision. Weight, waist circumference, body fat percentage, heart rate, blood pressure, VO2max, reaction time, grip strength, standing on one foot with eyes closed, sitting forward flexion, and quadrant jumping, the number of push-ups, quality of life (SF-36) score, and craving (VAS) scored were monitored in the HIIT and control groups at baseline, 4 months, and 8 months. SPSS 22.0 was used to perform repeated measures analysis of variance on the collected data of the subjects. RESULTS: Compared with baseline, weight (p<0.001), waist circumference (p<0.001), body fat percentage (p<0.001), heart rate (p<0.05), relaxation of HIIT group Pressure (p<0.01), systolic blood pressure (p<0.05), and VAS score (p<0.001) were significantly decreased after 8 months of exercise intervention. Contrastingly, VO2max (p<0.05), reaction time (p<0.001), grip strength (p<0.05), eyes closed and one foot Standing (p<0.001), sitting forward flexion (p<0.001), quadrant jumping (p<0.001), push-ups (p<0.001), PCS (p<0.001), and MCS (p<0.001) were significantly increased. CONCLUSION: 8-month HIIT can comprehensively enhance the physical fitness level and health-related quality of life of male methamphetamine abstainers, lower the craving for drugs and lay the foundation for a more successful reurn to society.